Heavy metal pollution characteristics and potential ecological risk assessment of soils around three typical antimony mining areas and watersheds in China - Qi, Yanting; Wei, Xiangdong; Zhao, MengJie; Pan, Weisong; Jiang, Chao; Wu, Jinbiao; Li, WaiChin (Frontiers in Environmental Science, 2022)
Three typical antimony mining areas were used as research districts to analyze the contents of heavy metals in soils of the mining areas and watersheds. The single-factor pollution index method, Nemerow comprehensive pollution index method, geo-accumulation index method, and potential ecological risk index method were used to comprehensively evaluate the pollution status and ecological risk of heavy metals in soils around the mining areas. The soil around the Lengshuijiang tin mine was polluted by As, Cd, Zn, and Sb, and the concentrations of the elements were 2.264, 14.07, 1.769, and 53.54 times of the national limit standards, respectively. The potential risk index was 852.1, indicating that it was a heavily polluted soil and at a high ecological risk level. The arable soil around the Nandan tea mountain antimony mine was polluted by As, Cd, Cu, Pb, Sb, and Zn, the concentrations of which were 101.9, 52.17, 1.896, 2.698, 77.48, and 8.93 times of the national limit standards, respectively. The potential risk index was as high as 3241, suggesting that it was a heavily polluted soil with very high ecological risk level. The soil around the Xunyang antimony mine was mainly polluted by Sb with a concentration of 19.49 times of the national limit standard and a potential ecological risk index of 175.6, indicating that it was a moderately polluted soil with moderate ecological risk level. The above results revealed that the overall soil heavy metal levels in the Lengshuijiang mining area and the Nandan mining area were in a high-risk state, most likely due to the mining and smelting of metal ores and the weathering of mineralised rocks. In addition, the three mining areas were all centred on the corresponding smelters and tailing areas. Within the same radius, the soil heavy metal pollution of the surrounding farmland and downstream arable land was more serious than that of each region’s upstream counterparts, and the pollution was worse at the river confluence point. Farther into the watershed, the pollution level gradually decreased but still far exceeded the national limit standard, showing a high-potential ecological risk in these mining areas.